2003
DOI: 10.1046/j.1538-7836.2003.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin mediates pathogenic effects of antiphospholipid antibodies

Abstract: Summary. Antiphospholipid (aPL) antibodies, detected in patients with antiphospholipid syndrome (APS) are associated with thrombosis, pregnancy loss and thrombocytopenia. Studies have shown that aPL are thrombogenic in vivo, but the mechanism(s) involved are not completely understood. Several studies have demonstrated that aPL antibodies activate endothelial cells (ECs) in vitro, as determined by up-regulation of adhesion molecules: E-selectin (E-sel); intercellular adhesion molecule-1 (ICAM-1) and vascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 36 publications
5
85
0
1
Order By: Relevance
“…Immunization of mice with β2GP1 or injection of human aPLA in mice increased thrombus size in murine thrombosis models and induced recurrent pregnancy loss. Thrombus formation was significantly reduced or abrogated in mice lacking the leukocyte adhesion molecules ICAM-1, E-selectin or P-selectin or by injection with anti-VCAM-1 antibodies [12,13]. These results imply that activation of the vascular endothelium by aPLA is a major thrombogenic mechanism [14].…”
Section: Cell Activation By Aplamentioning
confidence: 84%
“…Immunization of mice with β2GP1 or injection of human aPLA in mice increased thrombus size in murine thrombosis models and induced recurrent pregnancy loss. Thrombus formation was significantly reduced or abrogated in mice lacking the leukocyte adhesion molecules ICAM-1, E-selectin or P-selectin or by injection with anti-VCAM-1 antibodies [12,13]. These results imply that activation of the vascular endothelium by aPLA is a major thrombogenic mechanism [14].…”
Section: Cell Activation By Aplamentioning
confidence: 84%
“…Once endothelial cells become activated, up-regulation of TF may be further augmented by a synergistic effect of TNF-a and factor Xa [37]. Other changes typical for this prothrombotic phenotype include increased expression of adhesion molecules (ICAM-1, VCAM-1, selectins E and P) [38,39], and formation of endothelial microparticles [40]. Raschi et al have shown that anti-beta 2 GPI antibodies induce translocation of NFjB in a manner similar to that elicited by LPS and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown conclusively that aPL are thrombogenic in in vivo animal models (23)(24)(25). The prothrombotic properties of aPL may be explained in part by their ability to enhance the activation of platelets.…”
Section: Discussionmentioning
confidence: 99%